Diagnostic Value and Safety of Ultrasound-guided Needle Biopsy in Evaluation of Peripheral Lung and Mediastinal Nodules (Journal of Fatima Jinnah Medical University, 2018)
Background: Per-cutaneous needle biopsy is utilized next to imaging for the diagnosis of peripheral lung and mediastinal nodules. This is traditionally done under CT-guidance, which is not frequently available in resource-limited areas. Ultrasound (US) has been reported as a useful tool in evaluation of pleural or subpleural pulmonary nodules in the absence of an interposed aerated lung tissue and is reported as safe and effective tool for guided needle biopsies of masses abutting the chest wall in expert hands.1-3 This study aims to evaluate the diagnostic yield and safety of ultrasound-guided biopsy using Sure-Cut Needle.Methods: This prospective study was done in the department of Pulmonary Medicine, Gulab Devi Chest Hospital Lahore from March 2014 till June 2015.Total of 146 ultrasound-guided biopsies were evaluated. Only cases with peripheral lung nodules, pleural and mediastinal lesions were included. The Chest X-ray (CXR) PA and Lateral views were obtained. Point of biopsy was localized by consulting chest radiographs, CT films (if available) & chest sonography. Biopsy was done under aseptic technique after an informed consent. The specimens obtained underwent histopathologic evaluation.Results: Adequate samples were 97.94%, 89 cases (62.23%) were malignant, 54 cases (37.76%) were non-malignant. The sensitivity & specificity in diagnosing malignancy was 100%. The sensitivity for benign lesions is 100%, but specific disease characterization in benign issues is 87.04%. Biopsy-related complications were pneumothorax in 8.90%, haemoptysis in 7.53% and pain in 15 % patients.Conclusion: An ultrasound-guided needle biopsy of peripheral lung and mediastinal pathologies is a useful and safe modality with an excellent diagnostic yield and fewer complications.
Keywords: Sure-Cut needle biopsy, ultrasound-guided biopsy, mediastinal mass, peripheral lung nodule